2013
DOI: 10.1007/s10753-013-9769-x
|View full text |Cite
|
Sign up to set email alerts
|

Difference in LDL Receptor Feedback Regulation in Macrophages and Vascular Smooth Muscle Cells: Foam Cell Transformation Under Inflammatory Stress

Abstract: Macrophages and vascular smooth muscle cells (VSMCs) are the major cell types involved in foam cell formation associated with atherosclerosis. The aim of this experiment was to clarify cell-specific regulation of LDL receptor in THP-1 macrophages and human VSMCs under physiological and inflammatory conditions and its potential mechanisms. Inflammatory stress was induced by adding lipopolysaccharide (LPS) to human THP-1 macrophages and human VSMCs. Intracellular total cholesterol, free cholesterol, and choleste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
7
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…Therefore, macrophage LDLR expression may have a relevant impact in modulation of foam cell formation. The significance of this observation is highlighted by prior studies demonstrating the role of LDLR in inflammation‐induced unmodified LDL accumulation, 40,41 foam cell formation 39 and insensitivity of HFD‐induced atherosclerosis in response to loss of SR‐A and CD36 pathways 38 . In addition, our finding of increased phagocytic activity of BMM from L13a‐deficient mice vs controls (Figure 4D) is notable given the fact that phagocytosis is clearly involved in the pathogenesis of atherosclerosis, albeit with roles that are complex and currently not fully defined 42 …”
Section: Discussionsupporting
confidence: 62%
See 1 more Smart Citation
“…Therefore, macrophage LDLR expression may have a relevant impact in modulation of foam cell formation. The significance of this observation is highlighted by prior studies demonstrating the role of LDLR in inflammation‐induced unmodified LDL accumulation, 40,41 foam cell formation 39 and insensitivity of HFD‐induced atherosclerosis in response to loss of SR‐A and CD36 pathways 38 . In addition, our finding of increased phagocytic activity of BMM from L13a‐deficient mice vs controls (Figure 4D) is notable given the fact that phagocytosis is clearly involved in the pathogenesis of atherosclerosis, albeit with roles that are complex and currently not fully defined 42 …”
Section: Discussionsupporting
confidence: 62%
“…However, an alternative, scavenger receptor‐independent, 38 mechanism of lipid uptake, and foam cell formation mediated by native low‐density lipoprotein (LDL) has also been reported 39 . Supporting the potential importance of this pathway, several recent studies demonstrated a significant role of inflammatory stress in the native LDL uptake and LDL receptor (LDLR) mediated pathways of foam cell formation 40 and in disruption of a LDLR negative feedback loop 41 …”
Section: Resultsmentioning
confidence: 99%
“…However, CD36 is not the only mediator of oxLDL uptake. Other scavenger receptors for lipids, such as lectin-like oxidized LDL receptor-1 (LOX-1), low-density lipoprotein receptor-related protein (LRP1), and class A scavenger receptor (SR-A), internalize oxLDL and may be upregulated in VSMC by oxLDL [ 14 , 36 , 37 , 38 ]. On the contrary, the silencing of CD36 did not affect the upregulated expression of pro-inflammatory markers by HG and oxLDL, suggesting that the effects observed by the exposure to HG with or without the presence of oxLDL cannot be explained by the unique action of CD36-derived signaling.…”
Section: Discussionmentioning
confidence: 99%
“…Other tested conditions were cell starvation (0% fetal bovine serum [FBS] medium), which could increase LDLR levels (47), and the addition of unlabeled LDL, which could decrease LDLR levels (48)(49)(50). After 24 h of treatment, cell monolayers were incubated with VSV for 1 h at 4°C to examine VSV attachment by using Western blotting.…”
Section: Vsv Attachment To Hpaf-ii Cells Is Impairedmentioning
confidence: 99%